1999
DOI: 10.1046/j.1365-2443.1999.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐inducible SH2 protein‐3 (CIS3/SOCS3) inhibits Janus tyrosine kinase by binding through the N‐terminal kinase inhibitory region as well as SH2 domain

Abstract: Background: The Janus family of protein tyrosine kinases (JAKs) regulate cellular processes involved in cell growth, differentiation and transformation through their association with cytokine receptors. We have recently identified the JAK-binding protein, JAB that inhibits various cytokine-dependent JAK signalling pathways. JAB inhibits JAK2 tyrosine kinase activity by binding to the kinase domain (JH1 domain) through the N-terminal kinase inhibitory region (KIR) and the SH2 domain. The SH2 domain of JAB has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
333
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(354 citation statements)
references
References 30 publications
(52 reference statements)
12
333
0
3
Order By: Relevance
“…Thus, the specific pattern of the observed inhibition strongly suggests that Jak2-V617F is still sensitive to SOCS3-mediated inhibition. This also shows that the inhibitory mechanism is identical for Jak2-WT and Jak2-V617F, and corresponds to the mechanism extensively characterized by Sasaki et al (1999). Finally, using an siRNA approach, we found that both SOCS1 and SOCS3 can regulate Jak2-V617F expression levels ( Figure 6).…”
Section: Regulation Of Mutant Jak2 By Socs Proteinssupporting
confidence: 73%
“…Thus, the specific pattern of the observed inhibition strongly suggests that Jak2-V617F is still sensitive to SOCS3-mediated inhibition. This also shows that the inhibitory mechanism is identical for Jak2-WT and Jak2-V617F, and corresponds to the mechanism extensively characterized by Sasaki et al (1999). Finally, using an siRNA approach, we found that both SOCS1 and SOCS3 can regulate Jak2-V617F expression levels ( Figure 6).…”
Section: Regulation Of Mutant Jak2 By Socs Proteinssupporting
confidence: 73%
“…SOCS proteins are known to inhibit JAK activity by binding to JAK-proximal sites on cytokine receptors, which subsequently block access of STATs to a receptor-binding site on JAKs. 2,29 STAT3 is a transcription factor with oncogenic potential. There is growing evidence showing that STAT3 may play an important role in the pathogenesis of ALK þ ALCL, and that ALK and JAK3 contribute to STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS1 inhibits JAK kinase activation (Sakamoto et al, 1998), while SOCS3 inhibits JAK2 activity (Sasaki et al, 1999). Conse- Fig.…”
Section: Discussionmentioning
confidence: 99%